2018
DOI: 10.1590/1981-22562018021.180152
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malnutrition and associated factors in institutionalized elderly persons

Abstract: Objective : to evaluate the risk of malnutrition and associated factors in institutionalized elderly persons. Method : a cross-sectional study was carried out with elderly persons living in long-term care facilities in the municipal regions of Passo Fundo (Rio Grande do Sul) and Carazinho (Rio Grande do Sul) in 2017. A standardized, pre-codified questionnaire with sociodemographic variables was used, along with anthropometric data and the Mini Nutritional Assessment. Cognitive decline and non-intentional weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
0
0
7
Order By: Relevance
“…Still, there was no relationship between the HGS and chronic pain, but between the HGS and the factors gender and age. In this study, it was found that the profile of the institutionalized elderly consisted predominantly of private residents of LTCF, women, long-lived, widows and with education from 1 to 8 years 12 and that are in agreement with other studies 11,17,18 . With the considerable increase in the number of elderly people in recent times, musculoskeletal disorders, especially chronic pain, have been one of the main complaints among this population 19 , and in up to 80% of cases, these symptoms persist for at least two years until the search for treatment 20 .…”
Section: Discussionsupporting
confidence: 92%
“…Still, there was no relationship between the HGS and chronic pain, but between the HGS and the factors gender and age. In this study, it was found that the profile of the institutionalized elderly consisted predominantly of private residents of LTCF, women, long-lived, widows and with education from 1 to 8 years 12 and that are in agreement with other studies 11,17,18 . With the considerable increase in the number of elderly people in recent times, musculoskeletal disorders, especially chronic pain, have been one of the main complaints among this population 19 , and in up to 80% of cases, these symptoms persist for at least two years until the search for treatment 20 .…”
Section: Discussionsupporting
confidence: 92%
“…A atenção nutricional é um aspecto relevante atribuído a saúde do idoso, pois manter uma nutrição com vitaminas, oligoelementos, nutracêuticos e produtos naturais são essenciais para fortalecer o sistema imunológico e consequentemente, aumentar as defesas do organismo contra o COVID 19. Entretanto, com o avançar da idade os gostos e odores são sentidos com menor intensidade, devido a alterações fisiológicas nos órgãos sensitivos, o que pode gerar perda de apetite, escolhas alimentares erradas e desnutrição (14) .…”
Section: Fatores Fisiológicos Que Predispõem a Vulnerabilidade Do Idoso A Covid-19unclassified
“…Nesse estudo, foram mostrados enfermidades que podem ter sido a causa de desnutrição em idosos, sendo elas de ordem biológica e mental. As que foram associadas estatisticamente (Alzheimer, Declínio cognitivo, Doença periodontal, Depressão, Hipoalbuminemia e Anemia), encontram-se nos estudos de Nobre et al (2011); Damo et al (2018); Mesas et al (2010); Brock et al (2016); Silva et al (2012). , em uma revisão de literatura também encontraram enfermidades relacionadas com a desnutrição .…”
Section: Categoria B -Enfermidades Identificadasunclassified